(untitled) (Medico Legal Update, 2020)
Local, general, and regional anesthesia is complex actions or events that cannot be separated from elective or emergency surgery. Anesthesia affects the three thermoregulatory elements consisting of afferent input elements, signal regulation in the central region, and also the efferent response which can lead to hypothermia. This study aims to determine the effect of the use of aluminum foil blankets on increasing body temperature in hypothermia patients after spinal anesthesia. This study uses a Pre-Experimental study design with a PrePost Test Only Design approach. Sampling in this study used a purposive sampling technique. 12 samples were given the intervention to use aluminum foil blankets. Analysis of data using the Shapiro-Wilk test, Homogeneity of Lavene Test, and Paired sample T-Test. The results of statistical tests using the Paired Sample T-Test obtained a p-value of less than 0.05 (<0.05), namely p = 0.000. There is an influence of the use of aluminum foil blankets to increase body temperature in hypothermia patients after spinal anesthesia.